PENGEMBANGAN PRODUK YOGHURT BERBASIS LIMBAH KEJU DI RUMAH KEJU JOGJA (KEJUGJA) - Putri, Stevanie Primisari; Ranzani, Cut Dherra Widya Sari; Sihombing, Abi Mael; Fauzi, Yusuf; Onthoni, Maurits Calvin (LPPM Universitas Bina Bangsa, 2024)
Rumah Keju Jogja (KEJUGJA) is a cheese producer that requires approximately 1,200 liters of milk per month to produce its cheese. The whey waste generated during the cheese production process, amounting to 960–1,080 liters, is often discarded without optimal utilization, despite containing valuable nutrients. This study employs the Taguchi parameters to identify issues in whey waste management and process it into high-quality and financially viable yogurt. The method applied is the Taguchi Design of Experiments using an orthogonal array (OA) L9 to determine the optimal combination of factors affecting yogurt quality, namely milk, whey, and yogurt starter. The results of the Taguchi Design of Experiments indicate that the best combination for taste is 200 ml of milk, 200 ml of whey, and 20 g of yogurt starter, while for texture and thickness, the optimal combination is 300 ml of milk, 200 ml of whey, and 20 g of yogurt starter. The analysis of variance (ANOVA), conducted with α=0.05 and an f-table value of 5.14, reveals that no factor significantly affects yogurt quality at a 95% confidence level. From a financial perspective, the analysis shows that this yogurt product is not only economically viable but also has the potential to generate a net profit of IDR 78,967 from producing 25 cups per day. The breakeven point (BEP) indicates that selling 143 units of yogurt per month covers operational costs of IDR 1,721,040, with an investment payback period of IDR 1,672,000 achieved in approximately seven weeks. These findings emphasize the importance of innovation in waste management to enhance the sustainability and profitability of local cheese production businesses